ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI (Oriza sativa L) SAWAH TADAH HUJAN DI DESA NEGERI RATU BARU KECAMATAN BUNGA MAYANG KABUPATEN OKU TIMUR (JASEP, 2016)
This research was conducted in the village of Negeri Ratu Baru subdistrict Bunga Mayang East OKU, collecting data on the location of the research conducted in September and January 2017. The purpose of this study was to analyze factors that affect of production rainfed rice of Negeri Ratu Baru Bunga Mayang East OKU. The method used is a survey method. To analyze factors that affect of production rainfed rice using indicators BPS (2016). To examine the factors that affect the of production rainfed rice using multiple linear regression method. The Results showed the factors of production such as lending, seed, and fertilizer effect on production while the labor factor no real effect on the production of rainfed rice production, the average income of rainfed farm in the village Negeri Ratu Baru of 9.070.166/session.